Bridging the Gap between Grammar Knowledge and Writing Performance among EFL University Students - Sari, Mike Nurmalia; Saputra, Riyadi; Utami, Henny Septia (Journal of English Education and Teaching, 2025)
This study looks at how English as a Foreign Language students write and how that is connected to what they know about grammar. It focuses on three parts of grammar that English as a Foreign Language students need to know: how words are formed how sentences are put together and how to make sentences. The study involved 120 English as a Foreign Language students from an universities in Indonesia who are studying to be English teachers. To get the information needed the students took a test, on grammar. Also wrote an essay that was then analyzed. The results showed a significant positive correlation between grammar knowledge and writing performance (r = 0.624; p < 0.001), with syntactic knowledge as the strongest predictor. Regression analysis showed that grammar knowledge explained 32.9% of the variation in students' writing performance. These findings indicate that grammar mastery plays an important role but does not fully determine the quality of writing. Therefore, writing instruction needs to integrate grammar with rhetorical, lexical, and discourse skills through a contextual and process-based approach.